Pekkalotra: Pemberdayaan Perempuan Kepala Keluarga melalui Obat Tradisional Desa Menampu Kecamatan Gumukmas - Hadi Barru Hakam Fajar Siddiq; Dewi Riskha Nurmalasari; Kukuh Judy Handojo (Dental Agromedis, 2025)
The role of women in supporting the family economy is what is interesting. Women's roles are generally limited to domestic work, including caring for their husbands and children, cooking, and performing other household chores. Several factors encourage women to contribute to their families' economy. First, women who are left behind by divorce or the death of their husbands (widows). They need to work hard to meet the living expenses that are usually met by their husbands, especially for those with children. Given this condition, there are many programs that support women in developing their abilities, namely through women's empowerment programs. Women's empowerment programs that aim to increase women's awareness and potential to achieve independence in supporting the family economy, namely, through the empowerment program for women as heads of families using traditional medicines. This community service will last for five (5) weeks and will take place in Menampu Village, Gumukmas District. In this activity, participants will gain knowledge covering traditional medicine production and management, as well as the marketing of traditional medicine products. Community service activities through the empowerment of women heads of families (PEKKA) through traditional medicine have been implemented well. However, until this module was compiled, several stages had not been implemented, namely, continuous monitoring and assistance with traditional medicine product marketing strategies. Therefore, this activity needs to be continued so that it produces a more perfect output, namely, the independence and welfare of the Empowered Pekka Development Group.Keywords: Female heads of households, Empowerment, Traditional medicine